Increasing student engagement and retention using online learning activities wikis, blogs and webquests - Charles Wankel; Patrick Blessinger (Cutting-edge technologies in higher education ;, 2012)
Increasing Student Engagement and Retention using Online Learning Activities: Wikis, Blogs and WebQuests uses case studies, surveys, and literature reviews to critically examine how these technologies are being used to improve writing and publishing skills, student subject awareness, and literacy create engaging communities of practice, and as experiential learning tools. Chapters include ones on the design for a robust use of wikis, using blogs to enhance student engagement by creating a community of practice around a course, integrating blogs across a range of college level courses, publishing activist biographies on Wikipedia, using blogs to increase off-campus student engagement, using video and wiki technology to engage learners in large international cohorts, using wikis as an experiential learning tool, consuming and constructing knowledge through WebQuests, and rethinking WebQuests in second language teacher education. This volume will also discuss frameworks for deploying and assessing the effectiveness of these technologies.